(untitled) (Journal Of Educational and Psychological Researches, 2015)
When we study the history of dentistry we can investigate some methodology styles which lead us to psychology – dentistry or take the relationship between psychology and dentistry, and this type of specialization which is Medical psychology has its own methodology and subjects, as the historical sequence in this filed lead to how evolution occurred in this branch of medicine, which was accompanied by many factors , and this factor that contributed to the consolidation of the misconceptions about the social, family and the media culture and gave a distorted picture of Dentistry and the attending physician or dentist and show him as someone tough , ruthless and violent in his dealings and style , these problems lead to the creation of many symptoms and disorders on a patient who looks have many of the symptoms such as anxiety and fear that develops even phobia of the dentist. It have been proved that many of the studies and research that the loss of teeth leads to many cases of anxiety disorders , fears and this lead to the consolidation of a new psychology called psychology - dentistry and a branch of psychology stand - alone trying to create the field to correct concepts and false beliefs about dentistry in general and attempting to diagnose mental disorders and physical self- psycho-Somatic arising from them and try to draw a frame in which disorders arising from it are treated